Miniaturised band‐absorptive frequency selective rasorbers with wide absorption band. Issue 11 (2nd April 2019) - Yu, Weiliang; Luo, Guo Qing; Yu, Yufeng; Zhang, Xiao Hong; Fan, Kuikui
Abstract : Miniaturised band‐absorptive frequency selective rasorbers (FSRs) with wide absorption bands for single‐polarised and dual‐polarised applications are proposed here. These FSRs are both constructed by a lossy layer and a lossless layer, in which I‐type metal strips are utilised to reduce the size of the unit cell of the FSRs. The equivalent circuit models (ECM) of the FSRs are presented and analysed. A prototype of the dual‐polarised band‐absorptive FSR is fabricated, assembled, and tested. The measured results show that a wide absorption band (| S 21 |≤–10 dB and | S 11 |≤–10 dB) from 3.93 GHz to 8.07 GHz with a bandwidth of 69%, and a low‐pass band (| S 21 |≥–1 dB) with frequency lower than 880 MHz has been achieved for the dual‐polarised band‐absorptive FSR.